Evidence Based Review And Analysis On The Impact Of Orthodontic Intervention On Periodontal Clinical Attachment (Journal of Pharmaceutical Negative Results, 2022)
Background: By the means of this systematic review, we aimed to analyse the correlation present (if any) between orthodontic treatment modalities and their impact on periodontal clinical attachment levels. Methodology: Using the PRISMA framework, a thorough review of research that were listed in the PubMed, Web of Science, and Cochrane library databases was performed which revealed 103 papers, 54 of which were thoroughly evaluated. Exclusion and inclusion criteria were employed to choose studies that were applicable for our review, and finally we shortlisted 10 studies that were found to be suitable for the review. Results: No exact correlation could be drawn between orthodontic intervention and its subsequent impact on clinical attachment loss on the basis of the articles reviewed and thereupon statistical analysis. Conclusion: There is a significant lack of evidence that suggests orthodontic treatment’s impact on periodontal attachment, though it must be mentioned that further investigations in the future might unearth newer observations, and as such, the objective of our review is open to further debate.